Proceedings of the 2003 Bipolar/BiCMOS Circuits and Technology Meeting (IEEE Cat. No.03CH37440)
DOI: 10.1109/pac.2003.1289643
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of IGBT geometries, with the intention of mitigating undesirable destruction caused by fault scenarios of an adverse nature

Abstract: Megawatt class Insulated Gate Bipolar Transistors[IGBTs] find many uses in industrial applications such as traction drives, induction heating and power factor correction. At present, these devices are not optimized for higher speed pulsed-power applications, such as kicker magnets or klystron modulators.This paper identifies fundamental issues that limit the dIidt performance of standard commercial packages, and investigates several IGBT design optimizations that significantly improve high-speed performance at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A simulated rate of rise of current of between 7.5 kA/µs and 9.4 kA/µs was applied to the IGBT module. The simulations showed that the current density was greatest in IGBT B [2].…”
Section: A Slacmentioning
confidence: 95%
See 4 more Smart Citations
“…A simulated rate of rise of current of between 7.5 kA/µs and 9.4 kA/µs was applied to the IGBT module. The simulations showed that the current density was greatest in IGBT B [2].…”
Section: A Slacmentioning
confidence: 95%
“…The prototype solid-state induction modulator has been designed, built and tested at SLAC [2]. The manufacturer "A" IGBT modules in the modulator worked reliably during normal operation but many failed during an arc on the secondary.…”
Section: Testing Of Igbtsmentioning
confidence: 99%
See 3 more Smart Citations